ASPECTS OF FINANCIAL RATIO TOWARD STOCK RETURN ON TOURISM, HOTEL AND RESTAURANT SECTOR LISTED AT INDONESIA STOCK EXCHANGE - Marlyana Setiyani Muliasari; Lien Herliani Kusumah (International Humanities and Applied Science Journal, 2022)
This research aims to determine the effect of the Current Ratio (CR), Price Earning Ratio (PER), Net Profit Margin (NPM), Price Book Value (PBV) of the Stock Return on sub sector of tourism, hotels and restaurant listed in Indonesia Stock Exchange since 2012-2016. Research use secondary data and purposive sampling method. Data processing was performed using EVIEWS version 9 with fixed effect methode obtained based on Chow test and Hausman test. The results based on t-test showed that variable CR has negative insignificant effect on Stock Return, PER has negative significant effect on Stock Return, NPM has positive insignificant effect on Stock Return and PBV has positive significant effect on Stock Return. Based on coefficient determination as much 46% of variation variable stock returns can be explained by CR, PER, NPM, PBV while 54% on Stock Return variable variation explained by other factors. Keywords: Stock Return, Financial Ratio Aspects, Current Ratio, Price Earning Ratio, Net Profit Margin, Price Book Value